2010
DOI: 10.1155/2010/826585
|View full text |Cite
|
Sign up to set email alerts
|

UV Spectrophotometric Determination of Hydrochlorothiazide and Olmesartan Medoxomil in Pharmaceutical Formulation

Abstract: A simple, specific, accurate, precise and reproducible method has been developed and validated for the simultaneous estimation of hydrochlorothiazide and olmesartan medoxomil in combined dosage form by UV spectrophotometric method. UV spectrophotometric method includes simultaneous equation method (Method I) 271.5 nm and 257.0 nm λ max of both the drugs were selected, absorbance Ratio method (Method II) 261.5 nm an isoabsorptive wavelength and 257.0 nm were selected for estimation of hydrochlorothiazide and ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…These samples were then transferred to Costar clear 96-well plates and analyzed using a UV detector (SpectraMax M2, Molecular Devices, Pennsylvania, USA). Drug concentrations in the dissolution samples were determined based upon linear concentration-absorbance plots generated at 285, 250, 271, and 265 nm for CBZ, PHT, HCTZ, and CPM, respectively (24)(25)(26)(27).…”
Section: Dissolution Studiesmentioning
confidence: 99%
“…These samples were then transferred to Costar clear 96-well plates and analyzed using a UV detector (SpectraMax M2, Molecular Devices, Pennsylvania, USA). Drug concentrations in the dissolution samples were determined based upon linear concentration-absorbance plots generated at 285, 250, 271, and 265 nm for CBZ, PHT, HCTZ, and CPM, respectively (24)(25)(26)(27).…”
Section: Dissolution Studiesmentioning
confidence: 99%
“…Amlodipine besylate is official in IP [2] and BP [3] and Hydrochlorthiazide is official in IP [2], BP [3] and USP [4]. Literature survey revealed that various methods such as UV [9,10,15,16,19,20], HPLC [11,17], HPTLC [12,18], LC-MS/MS [13] and UPLC [14] are available in single and combination with other drugs. However, no spectrophotometric method has yet been reported for simultaneous estimation of amlodipine besylate, olmesartan medoxomil and hydrochlorthiazide in tablet dosage forms.…”
Section: Amlodipine Besylate (Figure 1a) [1] Is 3-ethyl 5-methyl (4rsmentioning
confidence: 99%
“…The numerous analytical methods dealt with assay of HCT, OLM, PRL, and AMD available [15][16][17][18][19][20] are impaired by inefficient or timeconsuming procedures and lack of statistical evaluation of significant variables. No HPLC method has been developed for simultaneous analysis of the four drugs so far.…”
Section: Introductionmentioning
confidence: 99%